Improving the Performance of Fog Computing Through the Use of Data Locality - Steffenel, Luiz Angelo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2018)
Fog computing extends the Cloud Computing paradigm to the edge of the network, developing a decentralized infrastructure in which services are distributed to locations that best meet the needs of the applications such as low communication latency, data caching or confidentiality. P2P-based platforms are good candidates to host Fog computing, but they usually lack important elements such as controlling where the data is stored and who will handle the computing tasks. As a consequence, controlling where the data is stored becomes as important as controlling who handle it. In this paper we propose different techniques to reinforce data-locality for P2P-based middlewares, and study how these techniques can be implemented. Experimental results demonstrate the interest of data locality on the data access performances.